Obtención de Azúcares Reductores a partir de Pasto Kikuyo (Pennisetum Clandestinum) - López Vásquez, Andrés Felipe; Ortegón Rey, Gabriell Alberto; Robles Rodríguez, Fredy Antonio (Avances Investigación en Ingeniería, 2010)
The production of reducing sugars by acid andenzymatic hydrolysis of Kikuyu grass was performedin order to study reducing sugar production. Thestudy involved hydrolysis of treated grass byimmersed in water at environmental temperatures.Acid hydrolysis was carried out through refluxboiling with different concentrations of dilutedsulphuric acid (2%, 4%, 6% v/v) with in a liquid/solid ratio of 30/1, while enzymatic hydrolysiswas carried out with stirring in a water/enzyme(celluclast 1,5 LFG) solution. Both procedureswere developed to different reaction times (2, 4and 6 hrs). Reducing sugars concentrations weredetermined by UV-Vis spectrophotometry usingthe 3,5 dinitrosalisilic acid (DNS) method. Also,Benedict qualitative test confirmed reducing sugarspresence in the samples. The greatest reducingsugars concentration was 2.5 g/l when using grasswith aqueous treatment, with a 4 % sulfuric acidsolution and 6 hours of reaction time. In general,results showed that greatest reducing sugarsconcentration were to high acid concentrations andreaction times.